Zonulin family peptide is not a predictive marker for development of minor postoperative complications: an observational study in patients after colorectal surgery - Agnes Knott; Alexander Müller; Gabriele Paul; Lampros Kousoulas; Roman Huber; Ann-Kathrin Lederer; Ann-Kathrin Lederer (Frontiers in Medicine, 2025)
BackgroundPostoperative complications after colorectal surgery are still challenging. Zonulin family peptide (ZFP) has been discussed as a potential marker of intestinal permeability and postoperative complications. The aim of this trial was to investigate whether ZFP allows early diagnosis of postoperative complications after colorectal surgery.MethodWe performed a monocentric, observational study among patients undergoing elective colorectal surgery between April 2018 and April 2019. Patients of all ages regardless of sex undergoing colorectal surgery without creation of ostomy were eligible for inclusion. Emergency surgery were not considered. Blood samples were taken preoperatively as well as on the 3rd, 6th and 9th postoperative day. All postoperative complications were classified according to Clavien-Dindo.ResultsOverall, 67 patients participated in the trial, 51% were male, average age was 58 years. Thirty-seven patients (55%) developed postoperative complications, mostly mild or moderate (Clavien-Dindo I and II). Almost all patients had a ZFP concentration in serum above the normal reference range preoperatively. Postoperatively, there was a significant decrease of ZFP on the 3rd postoperative day compared to the preoperative concentration of ZFP, but there was no association between ZFP levels and development of postoperative complications.ConclusionThe results suggest that ZFP is not able to predict minor postoperative complications after colorectal surgery.